A new species of Dixonius (Squamata: Gekkonidae) from the karst forest of Khammouane Province, central Laos - Nguyen, Thuong Huyen; Sitthivong, Saly; Ngo, Hanh Thi; Luu, Vinh Quang; Nguyen, Truong Quang; Le, Minh Duc; Ziegler, Thomas (Zootaxa, 2020)
A new species of Dixonius is described on the basis of three specimens from the karst forests around Thakhek town, Khammouane Province, Laos. The new species from Laos can be distinguished from other species of Dixonius based on molecular and morphological divergences. It is characterized by a maximum SVL of 55.4 mm; 20–23 longitudinal rows of dorsal tubercles at mid-body; 23–24 longitudinal rows of ventrals across the abdomen; 8–10 supralabials, 7 or 8 in mid-orbital position; 7 or 8 infralabials; 8 precloacal pores in male; the male without femoral pores; precloacal and femoral pores absent in females; uniformly pebble brown dorsum. In phylogenetic analyses, the new species is shown to be the sister taxon to two undescribed taxa from Thailand but differs by at least 8.6% in genetic pairwise distance from the latter based on the complete sequences of the mitochondrial ND2 gene with partial or complete sequences of six adjacent tRNAs. This is the ninth known species of Dixonius, and the second recorded species from Laos.